The Impact of Family Environment and School Environment on Entrepreneurial Interest Among 11th Grade Students at SMK Pustek Serpong South Tangerang - Fathia Puan Luthfia Arrifa, (International Journal of Economics Education Research (IJEER), 2024)
This study seeks to explore: (1) the impact of the family environment on the entrepreneurial interest of 11th-grade students students at PUSTEK Vocational High School, Serpong; (2) the impact of the school environment on their entrepreneurial interest students at PUSTEK Vocational High School, Serpong; and (3) the combined effect of the family and school environments on entrepreneurial interest among 11th-grade students at PUSTEK Vocational High School, Serpong. A quantitative method with an associative research design is used. The population includes 128 students, and Slovin's formula is applied to determine a sample size of 97 students. Data collection methods involve questionnaires with a Likert scale and observations. Data analysis utilizes both descriptive and statistical approaches. The findings reveal that the family environment significantly affects entrepreneurial interest, as shown by an R-square value of 0.263, meaning 26.3% of the variation in entrepreneurial interest is explained by the family environment, while 73.7% is impacted by other aspects not addressed in this research. Similarly, the school environment significantly impacts on entrepreneurial interest, with an R-square value of 0.244, showing that it accounts for 24.4% of the variation, leaving 75.6% influenced by other unexamined factors. When combined, the family and school environments have a notable effect, with an R-square value of 0.374. This indicates that together, these two environments describe 37.4% of the variation in entrepreneurial interest, whereas the rest 62.6% is ascribed to aspects outside the scope of this research.